They Can't Have My Embryo: The Ethics of Conditional Embryo Donation - Frith, Lucy (Bioethics, 2013)
There are substantial numbers of frozen embryos in storage that will not be used by those who produced them for their own fertility treatment. One option for such embryos is to donate them to others to use in their fertility treatment. There has been considerable debate about how this process should be organized. In the US, there are embryo adoption programmes that mediate between those relinquishing embryos and potential recipients. This is a form of conditional embryo donation, where the relinquishing couple can choose the recipient of their embryo. This article examines the ethical debate over conditional embryo donation for family building and explores the question of whether those who have unused frozen embryos should be able to determine who receives their embryos. The main objections to conditional embryo donation are examined: first, the embryo is not a person and therefore such concern over the placement of an embryo is unwarranted; secondly, potential donors might impose morally problematic conditions on who should receive their embryo; and thirdly, there are practical difficulties regarding organizational arrangements and the associated costs involved. It will be concluded that these objections can be countered and that if people wish to donate and receive embryos in this way there is no ethical objection to them doing so.